PENGARUH KOMUNIKASI INTERPERSONAL ORANG TUA DAN ANAK TERHADAP PRESTASI BELAJAR SISWA KELAS X - Muhammad Rofik; Agus Saifuddin Amin (Al-Amien Prenduan University, Sumenep, 2021)
Interpersonal communication is one of communication methods that often used for communicates with others, no doubt. The success of parents and teachers in communicating are the important one. Because they are humans that we should imitated. According to explanation above, the writer can take three conclusions from this research are:Based on this research to know available or not the influencw of interpersonal communication of parents to the achievement of students of class I MA Nurul Huda Pangilen Dasuk Sumenep Year 2017/2018, it can be shown by Thitung X1 2.589 > Ttabel 2.026. Hence thus the working hypothesis (H1) which states that